Knee Isokinetic Profiles and Reference Values of Professional Female Soccer Players - Isabel Brígido-Fernández; Francisco García-Muro San José; Guillermo Charneco-Salguero; José Miguel Cárdenas-Rebollo; Yolanda Ortega-Latorre; Ofelia Carrión-Otero; Luis Fernández-Rosa (MDPI AG, 2022)
Few studies have previously evaluated isokinetic parameters in female soccer players in comparison to those in males. The aim of this study was to describe normative quadriceps (Q) and hamstring (H) muscle strength values in professional female soccer players and to examine differences between dominant leg (DL) and nondominant leg (NDL). A standardized test protocol of concentric knee extension and flexion test protocol was conducted using the dynamometer isokinetic system (IsoMEd 2000). All the participants were healthy female professional soccer players from Spanish first and second division teams. Players were assessed for peak torque (PT) and maximum work (MW) values at 60°/s, 180°/s, and 240°/s. The mean difference was 7.17 (p-value = 0.0036), 4.4 (p-value = 0.0386), and 4.25 Nm (p-value = 0.0241) at speed 60°, 180°, and 240°/s, respectively. No statistically significant differences were detected for H-Q values between DL and NDL. This difference was 6.44 (p-value = 0.0449), and 5.87 J (p-value = 0.0266) at speed 60°, and 180°/s. The present study can be a tool that health professionals working with female professional soccer players in their care can use to assess and monitor a particular player.